Roles of sulfur-containing compounds in fermented beverages with 2-furfurylthiol as a case example - Zhang, Guihu; Xiao, Peng; Yuan, Mengmeng; Li, Youming; Xu, Youqiang; Li, Hehe; Sun, Jinyuan; Sun, Baoguo (Frontiers in Nutrition, 2023)
Aroma is a critical component of the flavor and quality of beverages. Among the volatile chemicals responsible for fragrance perception, sulfur compounds are unique odorants due to their extremely low odor threshold. Although trace amounts of sulfur compounds can enhance the flavor profile of beverages, they can lead to off-odors. Sulfur compounds can be formed via Maillard reaction and microbial metabolism, imparting coffee aroma and altering the flavor of beverages. In order to increase the understanding of sulfur compounds in the field of food flavor, 2-furfurylthiol (FFT) was chosen as a representative to discuss the current status of their generation, sensory impact, enrichment, analytical methods, formation mechanisms, aroma deterioration and aroma regulation. FFT is comprehensively reviewed and the main beverages of interest are typically baijiu, beer, wine and coffee. Challenges and recommendations for FFT are also discussed, including analytical methods and mechanisms of formation, interactions between FFT and other compounds, and the development of specific materials to extend the duration of aroma after release.